Motivasi Pemilihan Lintas Minat Biologi pada Siswa Jurusan Ilmu Sosial - Yendrita Yendrita; Elijonnahdi Elijonnahdi; Rian Utary Anggraini (BIOEDUSAINS: Jurnal Pendidikan Biologi dan Sains, 2019)
This study aims to determine the level of motivation of students majoring in Social Sciences (IS) in SMA N I Suliki District in choosing Biology cross-interests. Method, this research is quantitative with quantitative descriptive approach. Samples were taken by total sampling technique. The subjects in this study were all grade X students majoring in IS N NI High School in Suliki District who chose cross biology interest totaling 126 people, the data analysis technique was a percentage technique. The results of data analysis showed IS majoring students at SMAN 1 Kec. Suliki chose biology interest based on intrinsic motivation of 70.48% (good) and based on extrinsic motivation of 62.75% (good). Conclusion, the motivation of students majoring in Social Sciences (IS) in choosing cross-interests of biology both intrinsically and extrinsically is good. Keywords: social sciences, intrinsic motivation, extrinsic, cross biological Interests